Ethnobotanical uses of neem (Azadirachta indica A.Juss.; Meliaceae) leaves in Bali (Indonesia) and the Indian subcontinent in relation with historical background and phytochemical properties. (2nd August 2016) - Sujarwo, Wawan; Keim, Ary P.; Caneva, Giulia; Toniolo, Chiara; Nicoletti, Marcello
Abstract: Ethnopharmacological relevance: Neem ( Azadirachta indica ; Meliaceae ) is widely known for its cold pressed seed oil, mainly used as insecticide, but also for cosmetic, medicinal and agricultural uses. The seed oil is widely employed in the Indian subcontinent, and the leaves seem to have a lower relevance, but the ethnobotanical information of Bali (Indonesia) considers the utilisation of leaves for medicinal properties. Aim of the study: We report ethnopharmacological information about current uses of neem, in particular of the leaves, besides the insecticidal one, we discuss on the historical background of their uses. Materials and methods: Ethnobotanical data were collected using both literature and scientific references and semi-structured interviews with 50 informants (ages ranged between 14 and 76 years old) through the snowball method in thirteen aga (indigenous Balinese) villages, following Ethic code procedures. The informants were asked to specify: which part of the plant was used, and how that plant part was used. Plant specimens were collected, identified and made into herbarium voucher. In consideration of the high variability and complex chemical constituent of neem, a HPTLC analysis of neem leaves coming from both the Indonesian island of Bali and the Indian subcontinent was carried out. Results: The data on the medical use of traditional preparations from leaves of neem display a wide spectrum of applications. In the Indian subcontinent, neem leaves are used to treat dental and gastrointestinal disorders, malaria fevers, skin diseases, and as insects repellent, while the Balinese used neem leaves as a diuretic and for diabetes, headache, heartburn, and stimulating the appetite. Differences in utilisation cannot be related to chemical differences and other constituents besides limonoids must be investigated and related to the multipurpose activity of neem. Conclusion: This study revealed that neem leaves are believed to treat diabetes in both Balinese and Indian communities. Limonoids can not be considered the only responsible of digestive properties. Further research would be the validation of this report by enzymatic tests and the identification of active constituents. Graphical abstract: